4.7k views
0 votes
Hello, is it possible to have some help on this question?

Hello, is it possible to have some help on this question?-example-1
User IsaacHerb
by
4.5k points

1 Answer

5 votes

We have the following expression:


(-2+i)/(-4-5i)

By multiplying this expression above and below by the complex conjugate of -4-5i , we have


(-2+i)/(-4-5i)=(-2+i)/(-4-5i)*(-4+5i)/(-4+5i)

which gives


(-2+i)/(-4-5i)=((-2+i)(-4+5i))/(16+25)=(8-10i-4i-5)/(16+25)

which give us


(-2+i)/(-4-5i)=((-2+i)(-4+5i))/(16+25)=(8-10i-4i-5)/(16+25)=(3-14i)/(41)

Therefore, the answer is:


(-2+i)/(-4-5i)=(3)/(41)-(14)/(41)i

User Yann Armelin
by
4.4k points